Ancient judicial system of India - Sharma, Gokulesh (New Delhi, 2008)
Book Summary of Ancient Judicial System Of India Presents a collection of rules of ancient judicial system in India. This title is divided into 4 chapters that relate to ancient Indian political concepts and the functioning of the state and its administration. It describes the important provisions of civil laws, constitutional law, family law, and rules law.
Keywords: "Judicial system, Ancient - India"